Brewing Faith: How Coffee Shops in Garut and Bandung Foster Spiritual Growth and Community Connections - Kustanti, Dewi (FISIP UIN SGD Bandung, 2025)
This research explores the potential of coffee shops as informal venues for religious mentoring in urban communities, focusing on Garut and Bandung regencies. As public spaces increasingly shape social interactions and personal identities, coffee shops have emerged as modern hubs for both socializing and spiritual engagement. The aim of this study is to investigate how these informal settings contribute to religious and cultural growth by offering a platform for meaningful discussions on spirituality. Using a qualitative approach with a descriptive design, the study employs participant observation and semi-structured interviews to gather data from coffee shop patrons and owners involved in religious mentoring. The findings highlight that, beyond their role as social spaces, coffee shops can effectively foster religious dialogues, providing an accessible and relaxed environment for spiritual development. Mentors within these settings guide participants to integrate religious teachings into their daily lives, thus promoting a balanced lifestyle in a fast-paced urban context. This study offers insights into the evolving role of coffee shops in urban societies, suggesting that such spaces are not only conducive to casual interactions but can also serve as vital venues for spiritual engagement and growth. The research concludes that religious mentoring in coffee shops contributes to a more harmonious and spiritually enriched urban culture. Contribution: The insights gained from this study can inform future community-based spiritual initiatives, encouraging other urban areas to explore similar models. By leveraging the appeal of coffee culture, communities can create supportive environments for spiritual growth and cultural exchange.